Material properties of firefighter ladder composed from AA6063 and few other aluminium-based alloys - Hosova, Klara; Kubasek, Jiri; Strakova, Marketa; Necas, David (Manufacturing Technology Journal, 2020)
The sectional fire ladders, made of aluminium alloy AA6063, belong to the basic equipment of the fire department of the Czech Republic. The use of these materials facilitates the deployment of ladders for firefighting, but it also brings with it certain pitfalls. During the use of ladders in extinguish-ing fires, their thermal influence and subsequent changes in mechanical properties may occur. This is highly dangerous and can lead to people falling from these ladders due to a significant reduction in the mechanical properties of the material.
Keywords: Aluminium; firefighter ladder; microstructure; mechanical properties